PENGARUH PARTISIPASI MASYARAKAT, KUALITAS PELAYANAN PENGELOLAAN SAMPAH DOMESTIK DAN SOSIODEMOGRAFI TERHADAP TIMBULAN SAMPAH DI KECAMATAN MUARA SABAK BARAT KABUPATEN TANJUNG JABUNG TIMUR - Donal Ade Putra; Ilham Ilham; Ummi Kalsum (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Trash is one of the problems that are difficult to solve, trash is considered things that have been not to used again, the purpose of this analysis research factors that predispose level public participation with 3R concept, service quality, and sociodemography characteristics to lumps of trash, a dominant factor that predispose waste generation, and also a state of strategy trash management in districts of Muara Sabak Barat Kabupaten Tanjung Jabung Timur, the benefit of this research is as a suggestion and input for the public and trash managements. This Research uses the mix method sample of 193 respondents, this data analysis make measurements waste generation use of multiple linear regression. The number of trash generation in district Muara Sabak Barat on a day off ranges between 978–1.408 gr/day/KK, in weekdays ranging between 1.275-1.705 gr/day/KK, a while the average number of lumps on weekdays is 1.229 gr/day/people, on a day off between 1.558 gram/day/people. Generation rate district Muara Sabak Barat between 525 gr/day/people. The result Analysis multiple linear regression that is public participant (-0,07 gr/day/people), service quality (-6,29 gr/day/people), income (-194,91 gr/day/people) large of page (0.01 gr/day/people) and perception (9,91 gr/day/people). The dominant factor in domestic trash management to lumps of trash is income which is negatively worth 194,91 gr. This point shows that by assuming neglected other independent variables If every increase in income 1 (one) level then the lumps of trash will decrease by 194.91 gr.